2018
DOI: 10.1103/physrevlett.120.148003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Beads and Drops on a Repellent Solid Surface: A Unified Description

Abstract: We investigate freely expanding sheets formed by ultrasoft gel beads, and liquid and viscoelastic drops, produced by the impact of the bead or drop on a silicon wafer covered with a thin layer of liquid nitrogen that suppresses viscous dissipation thanks to an inverse Leidenfrost effect. Our experiments show a unified behaviour for the impact dynamics that holds for solids, liquids, and viscoelastic fluids and that we rationalize by properly taking into account elastocapillary effects. In this framework, the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…The radius of the dishes, R, and the height, h, are between 36 mm and 150 mm and between 8 mm and 40 mm respectively. The shear modulus of the gel is measured by indentation of a non-adhesive rigid sphere (diameter 6 mm at the surface of control samples fully covered with pure water in order to remove capillary forces [14][15][16]. For the experiments reported here, it lies between 10 and 160 Pa, a low value compared to modulus of ordinary rubber-like materials (µ ∼ 1 MPa), but comparable with the modulus of tissues (as liver or brain).…”
Section: Methodsmentioning
confidence: 96%
“…The radius of the dishes, R, and the height, h, are between 36 mm and 150 mm and between 8 mm and 40 mm respectively. The shear modulus of the gel is measured by indentation of a non-adhesive rigid sphere (diameter 6 mm at the surface of control samples fully covered with pure water in order to remove capillary forces [14][15][16]. For the experiments reported here, it lies between 10 and 160 Pa, a low value compared to modulus of ordinary rubber-like materials (µ ∼ 1 MPa), but comparable with the modulus of tissues (as liver or brain).…”
Section: Methodsmentioning
confidence: 96%
“…Next, we measure the deformation behaviour of the hydrogel spheres and introduce an energy decomposition similar to that used in (Zhao et al 2015b) to estimate the portions of the impact kinetic energy invested in each of sphere deformation and crater formation. Moreover, using this energy decomposition we show that the maximum deformation data can be collapsed by means of the introduction of an (elastocapillary) Mach number, in a manner similar to that done for hydrogel spheres impacting on a solid substrate (Tanaka, Yamazaki & Okumura 2003;Tanaka 2005;Arora et al 2018). Finally, we investigate the conditions under which the spheres rebound, and analyse them in terms of the spreading and impact time scales.…”
Section: Introductionmentioning
confidence: 94%
“…They showed that the spreading dynamics can be rationalized from a balance between inertia and bulk elasticity, E k = E e , where E k is the kinetic energy just before impact and E e is the elastic energy stored in the sphere at its maximum deformation, namely at the point where the kinetic energy can be assumed to be zero. Starting from the analysis described in Arora et al (2018), the stored bulk elastic energy is expressed as a function of the maximum deformation…”
Section: Impactor Deformation: Maximum Spreading Diametermentioning
confidence: 99%
See 1 more Smart Citation
“…Upon impact with the surface, the soft hydrogel sphere significantly deforms, as shown in the image sequence of figure 1c. We quantify this deformation using stretch λ and strain ε [32][33][34] (supplemental figure 6(a,b)).…”
mentioning
confidence: 99%